توازن الوصلة الخليوية في شبكات GSM - حسن عباس (Tishreen University, 2019)
Cellular link balance one of the main requirements for the GSM (Global System for Mobiles) networks, usually downlink is stronger than uplink at cell border which means link unbalance, this can be solved by TMA (tower mounted amplifier). The TMA is mounted on the antenna tower close to the receiving antennas, where it amplifies the received signal before it enters the antenna feeder. The amplification can be set stepwise and its maximum is about 10 dB for 900 MHz. This Research presents the results of the TMA trial on site-Town Hall159S4. The aim of the tests was to verify the effect of using a TMA on that rural site, applying the strategy described below. Main performance software ( BO ) tool and cell traffic recording were used to analyze the performance of the TMA. The goal of this research is to study the effect of using a TMA on cellular link balance. Main conclusions taken from this study are: The introduction of the TMA in the system leads to an improvement of the uplink performance in terms of drop call. The coverage was also increased. إن توازن الوصلة الخليوية هو أحد الشروط الضرورية للشبكة الخليوية الرقميةGSM وعادة تكون الوصلة الخليوية الهابطة أقوى من الوصلة الصاعدة في الشبكة الخليوية وذلك على حدود الخلايا وهذا يعني أن الوصلة الخليوية غير متوازنة وهذه المشكلة يمكن حلها عن طريق مضخمات يتم تركيبها على أبراج المحطات الخليوية وذلك بالقرب من هوائيات الاستقبال للمحطة الخليوية حيث يتم تضخيم الإشارة المستقبلة قبل أن تدخل إلى كبل الهوائي ويمكن التحكم بهذا التضخيم بشكل تدريجي ويبلغ حده الأعظمي حوالي  10 dBوذلك للشبكات الرقمية العاملة على التردد 900 MHz. يعرض هذا البحث نتائج تجارب مشروع استخدام المضخمات المركبة على برج هوائي المحطة المسماة Town Hall 159S4. ولقد كان الهدف من هذه الأختبارات التأكد من مدى تأثير المضخمات على أداء  المحطات الخليوية الريفية وذلك بتطبيق أستراتيجية مطبقة كما هو مبين في طريقة البحث أدناه. ولقد تم استخدام أداتين  برمجيتن الاولى تدعى الأداء الرئيسي (من شركة BO)  والثانية الاداة المسماة تسجيل حركة الخلية وذلك من أجل تحليل الإداء لمشروع المضخمات المركبة على الأبراج والهدف من هذا البحث هو دراسة التوازن القدروي للوصلة الهوائية الخليوية . والاستنتاج الرئيسي من هذه الدراسة : أن تركيب المضخمات على أبراج المحطات الخليوية يؤدي إلى تحسين إداء الوصلة الخليوية الصاعدة وذلك بالنسبة لعدد الاتصالات الخليوية غير الناجحة كما أن التغطية الخليوية تتحسن بشكل ملحوظ  .